مدى الإفادة من دلالة كلمة (قيل) في باب صلاة الجمعة في كتاب "منهاج الطالبين" ـ دراسة تحليلية توثيقيةـ - بابكر, ا.م.د. محمد أحمد; كه‌ره‌م, عبدالله قورباني (Sulaimani Journal for Humanities, 2023)
This research is entitled (The extent of benefiting from the significance of (it was said in the chapter on Friday prayer in the book Minhaj Al- Talibeen), and it consists of an introduction, two sections, and a conclusion. Through it, a brief overview of the life of Imam al-Nawawi, may God have mercy on him, and his scientific efforts, and his position among the scholars, becomes clear. Introducing the book “Minhaj al-Talibeen” in terms of its name, documenting its attribution to Imam al-Nawawi, may God have mercy on him, its subject matter, the reason for its composition, its abbreviation, its approach, may God have mercy on it, the date of its authorship, the number of its parts, its origins, its editions, its translation, the scholars’ praise for it and its scientific value. Then the research is a modest attempt to highlight the issues expressed by Imam al-Nawawi, may God have mercy on him, with (it was said) and attribute them to those who said them, with an indication of the extent to which it is possible to benefit from contemporary developments. The researcher followed the descriptive and analytical approach in this research, and the research ended with a conclusion containing the most important findings and recommendations.
Keywords: Imam alNawawi Minhaj alTalibeen alMinhaj term (was said)